What Could “Fair Allocation” during the Covid‐19 Crisis Possibly Mean in Sub‐Saharan Africa? - Moodley, Keymanthri (Hastings Cent Rep, 2020)
The Covid‐19 pandemic has sparked rapid and voluminous production of bioethics commentary in popular media and academic publications. Many of the discussions are new twists on an old theme: how to fairly allocate scarce medical resources, such as ventilators and intensive care unit beds. In this essay, we do not add another allocation scheme to the growing pile, partly out of appreciation that such schemes should be products of inclusive and transparent community engagement and partly out of recognition of their limited utility for physicians working in the field. Instead, we make the more modest claim that context matters when making such decisions and, more specifically, that recommendations from high‐income countries about fair allocation during Covid‐19 should not be cut and pasted into low‐income settings. We offer a few examples of why seemingly universal, well‐intentioned ethical recommendations could have adverse consequences if unreflectively applied in sub‐Saharan Africa.